Relation of Placenta Praevia with Previous Lower Segment Caesarean Section (LUCS) in our Clinical Practice - Parvin, Zebunnessa; Das, Sanjoy; Naher, Lutfun; Sarkar, Sumitendra Kumar; Fatema, Kaneez (Faridpur Medical College Journal, 2017)
Caesarean section (c-section) is one of the important risk factor to placenta praevia. There is significant association between placenta praevia and previous c-section pregnancy. It is a leading cause of APH and it affects approximately 0.5% of all labour. This cross sectional type of observational descriptive study based on non- probability technique was done in Faridpur Medical College Hospital from July 2015 - June 2016. A total of 150 pregnant women were studied. Pregnant women with H/O previous c-section once or more beyond 28 weeks gestation were included. Those who were primigravidae or pregnant women without previous c-section were excluded. The data were subjected to chi-square test with SPSS software version 20.0. In our study women with previous c-section were selected; out of which 16 patients (10.67%) were found to have placenta praevia and 134 patients (89.33%) were not found. The mean age of the study subject was 27.25 ± 3.43 years with maximum number of patients having age between 25 to 29 years. Among the study population other placental positions were anterofundal 90(60%) and posterofundal 44 (29.33%). The frequency of placenta praevia out of 16 women who had one c-section was 11 (10%), two c-section was 4 (11.4%) and three c-section was 1 (20%).There was significant association (p-value < 0.05) between number of c-section and placenta praevia. There was found significant relation between placenta praevia and lower segment caesarean section (LSCS) in our study. Faridpur Med. Coll. J. Jul 2017;12(2): 75-77